(untitled) (Strathmore Law Journal, 2021)
The Constitution of Kenya of 2010 adopts a bicameral legislative structure, within a devolved system of governance, consisting of the National Assembly and the Senate. In keeping with the devolved structure of government, the Senate’s legislative mandate is to a large extent confined to considering, debating and approving Bills concerning counties as well as determining the allocation of national revenue among counties and providing oversight over the national revenue allocated to the 47 county governments. Over the last ten years, Kenya has witnessed a great consolidation of power by the National Assembly at the expense of the Senate especially with regards to the roles of the chambers over the process of enacting the Division of Revenue Bill. Such consolidation of power attempts to relegate the Senate to a peripheral role within the bicameral legislative institutional structure. Consequently, the Supreme Court has asserted its advisory power and the High Court its judicial review power to mete out this inter-institutional conflict between the National Assembly and the Senate. This paper interrogates the manner Kenyan courts have discharged the contested role of serving as guardians of a legislative institution in a conflict within the bicameral legislative system. It makes the point that while courts have the authority to intervene in inter-cameral conflicts, judicial intervention should be exercised as an option of last resort, only utilised after exhaustion of the constitutionally ordained intra-parliament mediation process.